Sotagliflozin in Patients with Diabetes and Recent Worsening Heart Failure - Bhatt, Deepak L; Szarek, Michael; Steg, P. Gabriel; Cannon, Christopher P; Leiter, Lawrence A; McGuire, Darren K; Lewis, Julia B; Riddle, Matthew C; Voors, Adriaan A; Metra, Marco; Lund, Lars H; Komajda, Michel; et al. (The New England journal of medicine, 2021)
Patients with diabetes and recent worsening heart failure that had led to hospitalization were randomly assigned to receive sotagliflozin or placebo. At a median of 9 months, the total number of deaths from cardiovascular causes and hospitalizations and urgent visits for heart failure was significantly lower with sotagliflozin than with placebo.